Our overweight children : what parents, schools, and communities can do to control the fatness epidemic - Dalton, Sharron (California studies in food and culture, 2004)
The United States is facing a health crisis of epidemic proportions: children are gaining weight younger and faster than ever before. With the prospect of becoming the most obese generation of adults in history, they are already turning up with an alarming assortment of "grown-up" maladies, from type 2 diabetes to high blood pressure. This book takes a clear-eyed look at what's behind the statistics and diagnoses, and what can be done about the major health crisis among American children. Sharron Dalton begins with the basics: what obesity is, what causes it, and why it matters. Integrating in